Controllable fabrication of alginate/poly-L-ornithine polyelectrolyte complex hydrogel networks as therapeutic drug and cell carriers. (15th January 2022) - Xue, Wen; Liu, Bo; Zhang, Haipeng; Ryu, Sangjin; Kuss, Mitchell; Shukla, Devanshi; Hu, Guoku; Shi, Wen; Jiang, Xiping; Lei, Yuguo; Duan, Bin
Abstract: Polyelectrolyte complex (PEC) hydrogels are advantageous as therapeutic agent and cell carriers. However, due to the weak nature of physical crosslinking, PEC swelling and cargo burst release are easily initiated. Also, most current cell-laden PEC hydrogels are limited to fibers and microcapsules with unfavorable dimensions and structures for practical implantations. To overcome these drawbacks, alginate (Alg)/poly-L-ornithine (PLO) PEC hydrogels are fabricated into microcapsules, fibers, and bulk scaffolds to explore their feasibility as drug and cell carriers. Stable Alg/PLO microcapsules with controllable shapes are obtained through aqueous electrospraying technique, which avoids osmotic shock and prolongs the release time. Model enzyme and nanosized cargos are successfully encapsulated and continuously released for more than 21 days. Alg/PLO PEC fibers are then prepared to encapsulate brown adipose progenitors (BAPs) and Jurkat T cells. The electrostatic interactions between Alg and PLO are found to facilitate the printability and self-support ability of Alg/PLO bioinks. Alg/PLO PEC fibers and scaffolds support cell proliferation, differentiation, and functionalization. These results demonstrate new options for biocompatible PEC hydrogel preparation and improve the understanding of PEC hydrogels as drug and cell carriers. Statement of significance: In this study, the concept of polyelectrolyte complex hydrogel networks as drug and cell carriers has been demonstrated. Their feasibility to achieve sustained drug release and cell functionality was explored, from microcapsules to fibers to three-dimension printed scaffolds. PEC microcapsules with controllable shapes were obtained. Therapeutic drugs can be encapsulated and continuously release for more than 21 days. Benefiting from the dynamic interactions of physically crosslinked PEC, self-healing fibers were achieved. Besides, the electrostatic interactions between polyelectrolytes were found to facilitate the printability and self-support ability of PEC bioinks. The PEC fibers and scaffolds with controllable structure supported cell proliferation, differentiation, and function. The outcome of current research promotes design of new biocompatible PEC hydrogels and potential drug and cell carriers. Graphical abstract: Image, graphical abstract